Professional JavaScript frameworks : Prototype, YUI, Ext JS, Dojo and MooTools - Orchard, Leslie M. (Leslie Michael), 1975- ([Wrox]/Wiley Pub., 2009)
As the industry-standard, must-know scripting language, JavaScript is supported by all major browsers and is increasingly the foundation of new web development technologies such as Ajax and JSON. This book offers a selection of some of the most active and most used JavaScript frameworks available, replete with practical examples and explanations of what each framework does best. You'll look at common web development tasks and discover how each framework approaches that set of tasks, as well as learn how to use the features of each framework and avoid potential pitfalls.